2004
DOI: 10.1109/tps.2004.831758
|View full text |Cite
|
Sign up to set email alerts
|

Strength-Duration Curve for an Electrically Excitable Tissue Extended Down to Near 1 Nanosecond

Abstract: As part of a health and safety assessment of ultrawideband sources, it was useful to determine stimulation thresholds for an electrically excitable tissue down into the low nanosecond range. Stimulation thresholds were measured using gastrocnemius muscles isolated from 16 frogs (Rana sp.). Single pulses were delivered with a pair of surface electrodes, and muscle twitch was measured with an isotonic transducer. Pulse durations of 100, 10, and 1 ms; 100, 10 and 1 s; and 100 and 1 ns were used. Tissue voltage an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 23 publications
3
41
0
Order By: Relevance
“…For unipolar pulses of this nature, cell death can be induced with a significant drop in muscle contractions as compared to unipolar microsecond-long pulses [23]. Experimentally derived strength-duration curves indicate that a 100 ns pulse requires a voltage two orders of magnitude greater than a 10 µs pulse to excite muscle [37].…”
Section: Current State Of the Artmentioning
confidence: 99%
“…For unipolar pulses of this nature, cell death can be induced with a significant drop in muscle contractions as compared to unipolar microsecond-long pulses [23]. Experimentally derived strength-duration curves indicate that a 100 ns pulse requires a voltage two orders of magnitude greater than a 10 µs pulse to excite muscle [37].…”
Section: Current State Of the Artmentioning
confidence: 99%
“…Accordingly, nociceptor activation would play a critical role in immobilization. Other evidence suggests that TASER waveforms are capable of directly activating muscle in areflexive conditions [Rogers et al, 2004;Jauchem et al, 2006Jauchem et al, , 2008. Whether or not nociceptor activation has direct links to TASER immobilization, it is clearly an important component of TASER deterrence.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrashort pulses have been shown to exhibit exceptional safety factors, by some measures, and have the capacity to activate nociceptors and cause muscle twitching [Rogers et al, 2004;Nene et al, 2006]. It is likely that there are durations at which E-fields will no longer effectively couple to excitable tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Until the availability of pulses with UWB characteristics, die shortest durations of applied pulses were typically 10 jxs-l ms, e.g., [9], [36]. Recent research shows that voltage pulses of ~1 ns duration, or at least 10 000 times shorter than those previously studied, can stimulate excitable tissue when applied with sufficient amplitude directiy to the tissue preparation [37]. However, the lack of change in ECG intervals here indicated that energy coupled to tissue from the propagating UWB pulses was not capable of stimulating nerve cells or heart cells in a way that would cause a change in measured endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…(Abstracts 8,37,38,46;Publication 17) o Motor functions, locomotor activity, rearing activity, movement initiation and step test, tyrosine hydroxylase immunoreactivity in the striatum, microglial activation in the striatum, and lethality were used as endpoints. o Intravenous and subcutaneous dose response characteristics (0.0, 2.0, 2.5, 3.5 mg/kg/day) were assessed, o Lethality was dose and route dependent.…”
Section: Research On Neurotoxic Effects Of High Peak Power But Low Avmentioning
confidence: 99%